Protective effect of heat-processed Gynostemma pentaphyllum on high fat diet-induced glucose metabolic disorders mice - Jin-Bo Xie; Peng Xie; Mei Guo; Fang-Fang Li; Man-Yu Xiao; Yan-Shuang Qi; Wen-Jing Pei; Hao-Tian Luo; Yu-Long Gu; Xiang-Lan Piao (Frontiers Media S.A., 2023)
Glucose metabolic disorders (GMD) can promote insulin resistance (IR) and diabetes, and damage liver and kidney. Gynostemma pentaphyllum is commonly used in the clinical treatment of diabetes, but the research on its main active constituents and GMD has not been reported yet. This study explores the therapeutic potential of gypenosides of heat-processed Gynostemma pentaphyllum (HGyp) on high-fat diet-induced GMD in mice. HGyp was administered at different doses for 12 weeks. The investigation encompassed an array of parameters, including body weight, blood lipids, blood glucose, and liver tissue components. Metabolomic and network analyses were conducted to uncover potential targets and pathways associated with HGyp treatment. The results revealed that HGyp alleviated GMD by reducing body weight, blood glucose, and improving blood lipids levels, while increasing liver glycogen and antioxidant enzyme levels. Additionally, HGyp exhibited protective effects on liver and kidney health by reducing tissue damage. Fourteen blood components were detected by LC-MS. Metabolomic and network analyses indicated the potential engagement of the AGE-RAGE signaling pathway in the therapeutic effects of HGyp.Furthermore, Western blot and ELISA assays confirmed that HGyp upregulated GLO1 and GLUT4 while down-regulating AGEs and RAGE expression in liver tissue. In light of these findings, HGyp demonstrates promise as a potential therapeutic candidate for combating GMD, warranting further exploration in the development of therapeutic strategies or functional products.